2021
DOI: 10.1111/bju.15653
|View full text |Cite
|
Sign up to set email alerts
|

Minimally invasive treatments for benign prostatic hyperplasia: a Cochrane network meta‐analysis

Abstract: To assess the comparative effectiveness and ranking of minimally invasive treatments (MITs) for lower urinary tract symptoms (LUTS) in men with benign prostatic hyperplasia (BPH). Materials and MethodsWe searched multiple databases up to 24 February 2021. We included randomized controlled trials assessing the following treatments: convective radiofrequency water vapour thermal therapy (WVTT; or Rez um); prostatic arterial embolization (PAE); prostatic urethral lift (PUL; or Urolift); temporary implantable niti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 83 publications
1
22
0
Order By: Relevance
“…The patient had an IPSS of 29 points and a QOL score of 6. Transrectal ultrasonography revealed a 45-cm 3 PV. The patient had respiratory dysfunction due to chronic obstructive pulmonary disease, and after discussing various surgical options with him, he preferred PUL surgery under local anesthesia.…”
Section: Case Presentationmentioning
confidence: 98%
“…The patient had an IPSS of 29 points and a QOL score of 6. Transrectal ultrasonography revealed a 45-cm 3 PV. The patient had respiratory dysfunction due to chronic obstructive pulmonary disease, and after discussing various surgical options with him, he preferred PUL surgery under local anesthesia.…”
Section: Case Presentationmentioning
confidence: 98%
“…External stakeholders highlighted the need for reviews on minimally invasive treatments and desmopressin for lower urinary tract symptoms, for which there is a suite of Cochrane reviews [20,[22][23][24][25][26]. The CRG strategy for dissemination was co-publication of those reviews [22,[27][28][29], which has been shown to improve the impact of Cochrane reviews by reaching a highly specialized readership [30]. Moreover, both reviews have been cited in clinical practice guidelines.…”
Section: Final Editorial Prioritizationmentioning
confidence: 99%
“…Minimally invasive treatments result in broadly similar or less improvement in urinary symptoms and quality of life compared with TURP in men with BPE having moderate to severe symptoms as per a Cochrane network meta-analysis published in 2021 (27 randomised controlled trials, 3017 patients)910 (fig 2). Among minimally invasive procedures, PUL and prostatic artery embolisation (PAE) are likely to be more effective in reducing urinary symptoms.…”
Section: What Is the Evidence Of Uncertainty?mentioning
confidence: 99%
“…Retreatment rates with TURP tend to be lower overall (12 per 1000) compared with minimally invasive therapies. Higher retreatment rates were reported with transurethral microwave therapy (TUMT) 910…”
Section: What Is the Evidence Of Uncertainty?mentioning
confidence: 99%